Parametric modeling of under-5 children survival among 30 African countries: Lognormal accelerated failure time gamma shared frailty model - Bikis liyew; Kemal Tesfa; Kassaye Demeke Altaye; Abeje Diress Gelaw; Alemu Teshale Bicha; Ayanaw Guade Mamo; Kassaw Chekole Adane (PLoS ONE, 2025)
Background Under-five mortality continues to be a serious public health concern in low-and middle-income countries, particularly in Africa. This study investigates the probability of under-five survival and its predictors of mortality in the African continent using a recent demographic health survey from 2014–2022. Methods This study utilized recent Demographic and Health Survey data from 30 African countries, encompassing 226,862 live births. This study employed a multivariable lognormal accelerated failure time gamma shared frailty parametric survival regression analysis to identify the predictors of time-to-death among under-five children in these African nations. Result The overall under-five child mortality rate in Africa was 37.55 per 1,000 live births (95% CI: 37.35, 37.74. In this study, children born in Western Africa; children born in Eastern Africa; children born to mothers aged 15–19 years; maternal educational status; maternal decision autonomy; being female; place of delivery; number of ANC visits; children born among mothers who delivered by Cesarean section; mothers who have multiple birth outcome; children who were second birth order; and third birth order and third birth order; children who were small in size at birth; children who were born from a community with a low women education; having poor wealth index; respondents working; mothers delivered at the age between 20–35 were significant predictors of survival time to event of under-five children in Africa. Conclusion This study found that the overall under-five mortality rates remain high across Africa. In this study country region, maternal age, maternal education status, maternal age at first birth, respondent’s employment status, birth outcome, wealth index, birth order, place of delivery, mode of delivery, women’s autonomy in healthcare decision-making, number of antenatal care visits, child’s size at birth, sex of the neonate, and community-level women’s education were found to be significant predictors of survival time to death of under-five children. Addressing these multilevel factors is crucial for developing targeted interventions to reduce under-five mortality further and improve child survival in African countries.